Effect of academic stress on premenstrual syndrome - Bhavika Garg; Dr. Shikha Sharma (International Journal of Indian Psychȯlogy, 2022)
Background: Premenstrual Syndrome (PMS), is a common problem among girls, PMS is associated with various psychological, physiological and behavioral symptoms that leads to various social and work life impairments. Stress has been hypothesized as an important etiological factor of premenstrual symptoms. Academic stress may also be responsible for the increasing symptoms in college and school going students. The objective of this study was to study the effect of academic stress on symptoms of premenstrual syndrome. Objectives: To find the effect of academic stress on premenstrual syndrome. Methods: This is two group survey research studies among female college and school going students. The sample of 60 students was taken, and the data was collected by using Premenstrual Syndrome Scale (PMSS) and Student Stress Inventory (SSI). Correlation is used for statistical analysis. Results: The results shows that there is positive correlation between academic stress and premenstrual syndrome students having severe level of academic stress has shown severe level of symptoms of premenstrual syndrome while those with mild level of academic stress did not show the symptoms of premenstrual syndrome. Conclusion: Academic stress among the college going students have the impact on the intensity level of premenstrual syndrome. Thus academic stress can have effect on symptoms of premenstrual syndrome.